Importance of Probiotics in Fish Aquaculture: Towards the Identification and Design of Novel Probiotics - Edgar Torres-Maravilla; Mick Parra; Kevin Maisey; Rodrigo A. Vargas; Alejandro Cabezas-Cruz; Alex Gonzalez; Mario Tello; Luis G. Bermúdez-Humarán (Microorganisms, 2024)
Aquaculture is a growing industry worldwide, but it faces challenges related to animal health. These challenges include infections by parasites, bacteria, and viral pathogens. These harmful pathogens have devastating effects on the industry, despite efforts to control them through vaccination and antimicrobial treatments. Unfortunately, these measures have proven insufficient to address the sanitary problems, resulting in greater environmental impact due to the excessive use of antimicrobials. In recent years, probiotics have emerged as a promising solution to enhance the performance of the immune system against parasitic, bacterial, and viral pathogens in various species, including mammals, birds, and fish. Some probiotics have been genetically engineered to express and deliver immunomodulatory molecules. These promote selective therapeutic effects and specific immunization against specific pathogens. This review aims to summarize recent research on the use of probiotics in fish aquaculture, with a particular emphasis on genetically modified probiotics. In particular, we focus on the advantages of using these microorganisms and highlight the main barriers hindering their widespread application in the aquaculture industry.